Patient Decision-Making About Emergency and Planned Stoma Surgery for IBD: A Qualitative Exploration of Patient and Clinician Perspectives. Issue 2 (18th January 2018) - Dibley, Lesley; Czuber-Dochan, Wladyslawa; Wade, Tiffany; Duncan, Julie; Burch, Jennie; Warusavitarne, Janindra; Norton, Christine; Artom, Micol; O'Sullivan, Liam; Verjee, Azmina; Cann, Denise
Abstract: Background: Many inflammatory bowel disease (IBD) patients worry about stoma-forming surgery (SFS), sometimes enduring poor bowel-related quality of life to avoid it. Anticipation of SFS and whether expectations match experience is underreported. This qualitative study explored influences on patients' SFS decision-making and compared preoperative concerns with postoperative outcomes. Methods: We purposively recruited participants with IBD from UK hospital outpatient and community sources, and IBD clinicians from public hospitals. Four focus groups, 29 semistructured patient participant interviews, and 18 clinician interviews were audio recorded, transcribed, and analysed thematically. Participants had a current temporary, recently-reversed, or permanent stoma, or were stoma naive. Results: Four themes emerged: Preoperative concerns and expectations, Patient decision-making, Surgery and recovery, and Long-term outcomes. Participants and clinicians agreed about most preoperative concerns, that outcomes were often better than expected, and support from others with a stoma is beneficial. Patient decision-making involves multiple factors, including disease status. Some clinicians avoid discussing SFS, and the phrase 'last resort' can bias patient perceptions; others recommend early discussion, increasing dialogue when medical management becomes ineffective. The postoperative period is particularly challenging for patients. Stoma acceptance is influenced by personal perceptions and pre- and postoperative clinical and social support. Conclusion: Patients need balanced information on all treatment options, including surgery, from an early stage. Early multidisciplinary team dialogue about SFS, and contact with others living well with a stoma, could enable informed decision-making. Life with a stoma is often better than anticipated, improving quality of life and control. Ongoing specialist nursing support aids recovery and adjustment.